Pengaruh Konsumsi Nugget Ikan Tuna Terhadap Perubahan Berat Badan Balita Di Desa Percut Sei Tuan - Evi Martina, Siska; Awidiyah; Tiur Gultom (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2022)
During childhood, the process of growth and development takes place very quickly, hence the need for adequate nutrition. Food intake is one of the direct causes that affect the nutritional status of young children. The prevalence of very poor and poor nutritional status in toddlers in Dusun 2 Percut Sei Tuan Village is 2.74% and has not reached the target of 1.0 SD (prevalence) of malnourished toddlers selected from 15 respondents using purposive sampling technique. The research site was Posyandu Dusun 2 Percut Sei Tuan Village. Questionnaires and weight measurements were used to collect data. STATA 14 with paired T test was used for data processing and analysis. Based on the results of the study, the average body weight of toddlers before the intervention was 13.56 ± 3.08 and the average body weight after the intervention was 14.28 ± 2.99. The results of the paired T test analysis have a Sig value. (2-tailed) 0.000 <0.05, indicating that Tuna Fish Nuggets can affect weight change in young children. The conclusion of this study is that the average body weight changes before and after the Tuna Fish Nugget intervention with an increased change of 0.38 kg.